Shell structure and composition alterations in the limpet Lottia subrugosa along a contamination gradient in the Santos Estuary, Brazil - Oliveira, Carolina Rocha Moreira (2020)
Molluscs have been widely used in biomonitoring of aquatic environments because they are highly sensitive to hazardous chemical substances and have the capacity to express the history of environmental changes in their shells. Mollusc shells have biomolecules playing an essential role in the biomineralization process, which are also susceptible to environmental stressors that promotes chemical and structural alterations. Thus, the present study evaluated structural and compositional shell changes in the limpet Lottia subrugosa along a spatial contamination gradient in Santos Estuary. Results showed that organisms collected in more contaminated sites presented shells more fragile, with a reduction of thickness in the prismatic layer associated with the enlargement of the periostracum layer. In addition, a significative reduction in the organic fraction amounts, including a decrease in protein content, was observed in shells of organisms from the most contaminated site. An opposite pattern was also observed at sites under the influence of lower contamination rates. Moreover, our results suggested that limpets inhabiting contaminated environments might be more vulnerable to predatory pressures due to the increase in shell fragility. The core set of endpoints tested in field conditions by the present study appears to be promising environmental assessment tools.